2019
DOI: 10.1200/jco.2019.37.4_suppl.433
|View full text |Cite
|
Sign up to set email alerts
|

A new clinically based staging system for gallbladder cancer.

Abstract: 433 Background: Current staging systems for gallbladder cancer (GBC) are inadequate, as they are based on surgical pathology, and therefore are not relevant for unresectable patients and patients undergoing neoadjuvant chemotherapy. Methods: Patients with a confirmed diagnosis of GBC who were seen at Mayo Clinic between the years 2000 and 2016 were included in this analysis. Data on demographic and tumor characteristics and outcomes were collected by retrospective review of electronic medical records. A model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Several studies several studies have found that tumor size may be an independent prognosis factor in GBC, which is in line with our study, however, debate also exists regarding the optimal cutoff value of tumor size in GBC. Yadav et al reported that tumor size larger than 5 cm exert prognostic signi cance for GBC patients 8 . Zhang et al demonstrated that tumor size smaller than 3 cm obviously increase the survival outcome of GBC patients 7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies several studies have found that tumor size may be an independent prognosis factor in GBC, which is in line with our study, however, debate also exists regarding the optimal cutoff value of tumor size in GBC. Yadav et al reported that tumor size larger than 5 cm exert prognostic signi cance for GBC patients 8 . Zhang et al demonstrated that tumor size smaller than 3 cm obviously increase the survival outcome of GBC patients 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The wideaccepted standard Tumor-Node-Metastasis (TNM) staging system of the American Joint Commission on Cancer (AJCC) mainly relies on pathological evaluation of tumor in ltration into the layers of gallbladder, which can only be achieved through surgical excision of the gallbladder and didn't take tumor size into account 6 . The recent studies, which proposed prognostic nomograms/systems, pointed out that patient and tumor-related factors are closely associated with prognosis of GBC patients 7,8 . Notably, several studies have found that tumor size, as an easily quanti able indicator in imaging diagnosis and preoperative assessment, can affect the survival outcome of GBC patients [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, prognostic prediction of MBT mostly based on the AJCC TNM staging system [6], which mainly based on surgical pathology features including tumor size, lymph node metastasis and distant metastasis, regardless of clinical and laboratory parameters. Previous studies also proposed several staging systems including clinical parameters such as hemoglobin, alkaline phosphatase and C reactive protein, but showed a suboptimal correlation with survival or lack of validation, such as the GBC staging system created by Yadav S, et al [7]. Therefore, new prognostic factors with better predictive capability for BMT patients are needed.…”
Section: Introductionmentioning
confidence: 99%